Upper lip cross sectional area after correction of anterior maxillary segment using three sided mucoperiosteal flap (Mustansiria Dental Journal, 2005)
Abstract:All previous studies concerning the soft tissue changes associated with upperjaw osteotomy related to the use of the most common approaches to the anteriormaxilla i.e. Wassmund, Wunderer and Cuper approach. Few of these directed toassess the upper lip cross sectional area as a factor in prediction pmpose. A newapproach by mean of 3-sided mucoperiostcal flap adopted in this study to expose thepremaxilla. From the clinical observation, there is slight lengthening ofthe upper lipafter surgery.This study conducted to assess the upper lip cross sectional area aftermaxillary segmental setting up osteotomy using this approach(for prediction purpose),and assess the validity of the use of the 3-sided mucoperiosteal flap.Presurgical and post surgical cephalometric radiographs of (9) patients werecompared by superimposition of acetate tracings on special references. Crosssectional lip area then calculated presurgically and at two intervals following surgicalintervention (immediately after surgery i.e. with in 2 days and the longest possiblepost surgical follow up) using simpson role.Analysis of data showed that the cross sectional lip area significantlyincreased by a mean of 38% ranged (23% - 58%) immediately after surgery. While atabout 3 months interval, it became about 17% ranged (2% — 34%) the study showedalso an acceptable accessibility with the use of this 3-sided flap.